The dynamic behaviour of symmetrical laminated nano-composite containing equal numbers of glass and carbon fibre layers - Mohammed, Ava A. K. (Strojniški vestnik, 2023)
Fibre-reinforced polymer composite has many uses in structural components that required high strength, stiffness, and damping capacity. Cross and quasi-laminated epoxy composites with and without nano Al2O3 were used in this investigation to determine flexural modulus, natural frequency, damping ratio, and mode shapes by using analytical, experimental, and numerical (ANSYS) methods. It was demonstrated that adding 2 % nano Al2O3 improved the flexural modulus and the damping ratio while decreased the natural frequency. Cross number 2 and quasi number 2 had the highest natural frequency for cross and quasi laminate groups which are equal to 23.5 Hz and 20.25 Hz experimentally, respectively. On the other hand, the higher damping ratio was achieved for cross number 1 with nano Al2O3 and quasi number 2 with nano Al2O3 for both cross and quasi laminates, which are equal to 0.707 % and 0.693 %, respectively. The flexural modulus and damping ratio are inversely related to each other. However, the novelty in this article is that by adding two glass plies at the outer surface of quasi group laminate the flexural modulus, natural frequency, and damping ratio are increased simultaneously, as in the configurations quasi number 2 and quasi number 2 with nano Al2O3 in comparison with quasi number 1 and quasi number 1 with nano Al2O3.
Keywords: cross laminate; damping ratio; faktor dušenja; križni laminat; kvazi laminat; lastna frekvenca; modul elastičnosti pri upogibu; nanodelci; nanoparts; natural frequency; quasi laminate